Roles, challenges and effectiveness of Majlis Agama Islam Selangor (MAIS) in wasiyah management in Selangor / Syasya Syuhada Esa - Esa, Syasya Syuhada (Academy of Contemporary Islamic Studies (ACIS), 2016)
Since era of sahabah (Khulafa ar-Rashideen), institution of Baitul Mal was established as a financial institution and central repository of national treasures which act as a platform in management of treasure and property to develop economy of muslim at that time. However, in Malaysia, roles of institution of Baitul Mal no longer be an institution that regulates and supervises national treasure and property holistically because it is bound to act as it has been designated under the federal constitution and now it is managed by Majlis Agama Islam Negeri (MAIN). In Selangor, Majlis Agama Islam Selangor (MAIS) act as Baitul Mal to promote, drive, assist and initiating the economy and social development and well-being of muslim community in line with syarak. Therefore, in this study is aimed to analyze the effectiveness institution of Baitul Mal that organized by MAIS in wasiyah management in Selangor. In addition, this study also discusses the mechanisms and methods Baitul Mal (MAIS) in wasiyah management in Selangor. The study also focuses on the role of MAIS in wasiyah management in Selangor as an institution of Baitul Mal in Selangor. Study methodology for this study is from libraries studies, the data collection come from primary and secondary data, analysis of data achieve from analyse all data find out from data collection.